2021
DOI: 10.3390/ijms22031143
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Neutrophils in the Thrombosis of Chronic Myeloproliferative Neoplasms

Abstract: Thrombosis is a major cause of morbimortality in patients with chronic Philadelphia chromosome-negative myeloproliferative neoplasms (MPN). In the last decade, multiple lines of evidence support the role of leukocytes in thrombosis of MPN patients. Besides the increase in the number of cells, neutrophils and monocytes of MPN patients show a pro-coagulant activated phenotype. Once activated, neutrophils release structures composed of DNA, histones, and granular proteins, called extracellular neutrophil traps (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 86 publications
0
17
0
3
Order By: Relevance
“…Indeed, higher CD177 expression was associated with an increased risk of thrombotic and bleeding complications due to increased circulating neutrophils [ 173 , 174 ]. For a complete and recent review on the role of neutrophils in thrombosis, we refer readers to the article by Ferrer-Marín and colleagues published in this special edition [ 175 ]. It is clear that we need to further elucidate the molecular mechanisms of leukocyte–platelet interactions in order to design better prophylactic treatment plans for the prevention of thrombotic complications in patients with PV.…”
Section: Prognosismentioning
confidence: 99%
“…Indeed, higher CD177 expression was associated with an increased risk of thrombotic and bleeding complications due to increased circulating neutrophils [ 173 , 174 ]. For a complete and recent review on the role of neutrophils in thrombosis, we refer readers to the article by Ferrer-Marín and colleagues published in this special edition [ 175 ]. It is clear that we need to further elucidate the molecular mechanisms of leukocyte–platelet interactions in order to design better prophylactic treatment plans for the prevention of thrombotic complications in patients with PV.…”
Section: Prognosismentioning
confidence: 99%
“…Recent studies have described the relationship between the mechanisms and immune responses expressed by cells involved in the innate and adaptive immune system (neutrophils, monocytes, macrophages, lymphocytes, endothelial cells and platelets) with important molecules of hemostasis, which is a phenomenon currently called immunothrombosis. The immunothrombosis process is multifactorial, generally mediated by hypercellularity, and causes changes in plasma proteins that are important in the process of hemostasis and activation of endothelial molecules, adhesion product and cell function [ 49 , 50 , 51 ]. Hypercellularity in peripheral blood is a result of the constitutive activation of the JAK2/STAT5 pathway, which increases blood viscosity through cell–cell–endothelial interaction, and even forms plasma complexes [ 49 , 50 , 51 , 52 , 53 ].…”
Section: Implications Of the Jak2 V617f Variant In...mentioning
confidence: 99%
“…The immunothrombosis process is multifactorial, generally mediated by hypercellularity, and causes changes in plasma proteins that are important in the process of hemostasis and activation of endothelial molecules, adhesion product and cell function [ 49 , 50 , 51 ]. Hypercellularity in peripheral blood is a result of the constitutive activation of the JAK2/STAT5 pathway, which increases blood viscosity through cell–cell–endothelial interaction, and even forms plasma complexes [ 49 , 50 , 51 , 52 , 53 ]. Thus, the characteristic leukocytosis, erythrocytosis and thrombocytosis in patients with MPNs not only reflect quantitative alterations in hematopoiesis, but also qualitative alterations in the immune response and hemostasis, through the expression of molecules that favor the activated prothrombotic phenotype [ 50 ].…”
Section: Implications Of the Jak2 V617f Variant In...mentioning
confidence: 99%
“…Generally, they are formed by neutrophils upon the release of chromatin together with components of their membrane and granules, which subsequently leads to sequestration of erythrocytes and thrombocytes and activation of the coagulation cascade. Despite the potential relevance of NET formation in MPN, the current literature is not entirely clear on its role, as reviewed by Ferrer-Marín et al [103]. Of the three studies conducted on samples obtained from MPN patients, only one demonstrated increased NET production by neutrophils [99,[103][104][105]].…”
Section: Inflammation and Neutrophilic Granulocytes In Mpnmentioning
confidence: 99%
“…Despite the potential relevance of NET formation in MPN, the current literature is not entirely clear on its role, as reviewed by Ferrer-Marín et al [103]. Of the three studies conducted on samples obtained from MPN patients, only one demonstrated increased NET production by neutrophils [99,[103][104][105]]. An explanation for this discrepancy may lie in the fact that JAK2 inhibitor treatment appears to downregulate NET formation, and several patients of the two negative studies received treatment with JAK2 inhibitors [103].…”
Section: Inflammation and Neutrophilic Granulocytes In Mpnmentioning
confidence: 99%